Mitochondrial regulation of NADPH oxidase in hindlimb unweighting rat cerebral arteries. - Ran Zhang; Hai-hong Ran; Liang Peng; Fei Xu; Jun-fang Sun; Lan-ning Zhang; Yong-yan Fan; Li Peng; Geng Cui (PLoS ONE, 2014)
Exposure to microgravity results in post-flight cardiovascular deconditioning and orthostatic intolerance in astronauts. Vascular oxidative stress injury and mitochondrial dysfunction have been indicated in this process. To elucidate the mechanism for this condition, we investigated whether mitochondria regulated NADPH oxidase in hindlimb unweighting (HU) rat cerebral and mesenteric arteries. Four-week HU was used to simulate microgravity in rats. Vascular superoxide generation, protein and mRNA levels of Nox2/Nox4, and the activity of NADPH oxidase were examined in the present study. Compared with control rats, the levels of superoxide increased in cerebral (P<0.001) but not in mesenteric vascular smooth muscle cells. The protein and mRNA levels of Nox2 and Nox4 were upregulated significantly (P<0.001 and P<0.001 for Nox2, respectively; P<0.001 and P<0.001 for Nox4, respectively) in HU rat cerebral arteries but not in mesenteric arteries. NADPH oxidases were activated significantly by HU (P<0.001) in cerebral arteries but not in mesenteric arteries. Chronic treatment with mitochondria-targeted antioxidant mitoTEMPO attenuated superoxide levels (P<0.001), decreased the protein and mRNA expression levels of Nox2/Nox4 (P<0.01 and P<0.05 for Nox2, respectively; P<0.001 and P<0.001 for Nox4, respectively) and the activity of NADPH oxidase (P<0.001) in HU rat cerebral arteries, but exerted no effects on HU rat mesenteric arteries. Therefore, mitochondria regulated the expression and activity of NADPH oxidases during simulated microgravity. Both mitochondria and NADPH oxidase participated in vascular redox status regulation.